IMPLEMENTASI ALGORITMA WINNOWING UNTUK MENDETEKSI KEMIRIPAN PADA DOKUKEN TEKS - Obed Kharisman; Budi Susanto; Sri Suwarno (Jurnal Informatika, 2013)
Plagiarism is one of the main problems which the academic world must cope with recently. Many student papers and assignments had been found containing lines or sentences directly copied or sourced without sufficient acknowledgments to their original authors. Based on this fact, this research is conducted by developing software capable of detecting similarity between text documents, using “Winnowing algorithm” which is a document fingerprinting algorithm. The goal of this research is to measure its effectiveness in comparing test documents and reporting their similarity by percentage.